Pengaruh Variasi Gaya Mengajar Guru terhadap Motivasi Belajar Siswa di SDN 158367 Laemonong 2 - Eni Nurhalizah Gajah; Sorta Simanjuntak (Journal on Education, 2023)
This study is aimed at knowing the effect a variety of teacher teaching styles can have on students' learning motivation in SD Negeri 158367 Laemonong 2 in the district Manduamas, Tapanuli Tengah. As for this type of research, it is a quantitative study with an ex-post facto method (research that examines a particular of situation). The population of this study is the total of student at the SD Negeri 158367 Laemonong 2, which is 107 students, with the sample taken with 40 students. The data collection in the study uses a questionnaire of variety of teaching styles and student learning motivation. The questionnaire consisting of 4 likert-scale answers, and analysis requirements test in the study with a normality test, linear homogeneity and regression test. And data analysis in this study uses descriptive analysis, hypothetical tests, significance tests and determinations. Regression analysis shows a simple linear regression equation on the research which is y = 25.718 + 0.514x which suggests that each additional one unit of elimination of the variety of teaching style will be followed by an increase of 0.514 on the student's learning motivation level. In addition, r square measures 0.1874 or 18.74%. Based on data analysis it shows that there is a positive and siginiffish between the variety of teaching styles and student learning motivation at SDN 158367 Laemonong 2. By showing rxy of 0.433 classified into group moderate with t-count (2.965) > t-table (1.685). And in the variations in teacher teaching styles falls into the moderate category with an average score of 71,625 and deviation standard of 3.691. And student learning motivation falls into the moderate category with an average score of 62.550 anda standard deviation of 4.379.